Implikasi KMB dalam Meningkatkan Proses Pembelajaran PAI Siswa MTS Gintangan - Rahman, Fazlur Mujahid; Asmuni, Hadiqoh; Habibah, Nur Faiz (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2024)
This research aims to explore the impact of the independent learning curriculum in the PAI learning process. This research uses a quantitative approach method which is based on data collection and analysis in the form of numbers. The data sources used are secondary data and primary data. In the data validity technique in this research, researchers used the Chi-quadrat test. Based on the results of research at MTs Gintangan, it can be concluded into three main points, including: 1) There is a connection between KMB and increasing the PAI learning process for MTs Gintangan students. 2) The more effective the application of KMB in learning, the greater the opportunity to improve students' understanding of the material. 3) There is a connection between KMB and increasing student motivation, which means that the more effective the application of KMB in learning, the higher the chance of increasing student motivation. This research provides recommendations for all parties involved in implementing KMB in their respective schools.